Condensation heat removal due to the combined impact of natural convection and radiative cooling - Tsoy, Alexandr; Granovskiy, Alexandr; Nurakhmetov, Baurzhan; Koretskiy, Dmitriy; Tsoy-Davis, Diana; Veselskiy, Nikita (Eastern-European Journal of Enterprise Technologies, 2023)
The work examines the heat exchange characteristics of a condenser in which heat removal of the refrigerant condensation occurs due to natural convection and radiation cooling. The heat exchanger is designed to reduce energy costs for the removal of condensation heat. Unlike traditional air cooling condensers, it uses radiation cooling, a method of heat removal based on its transmission in the form of infrared radiation through the planet’s atmosphere into the surrounding outer space. A method for calculating the thickness of the radiating plate has been developed. To minimize material consumption and cost, the distance between the tubes is reduced to 40 mm, and the thickness of the aluminum radiating plate is reduced to 0.32 mm. The inner diameter of the coolant channels is 1 mm. For the experimental study of the condenser, an experimental stand working on R134a refrigerant was developed. Theoretical and experimental studies of heat transfer have been carried out. The heat transfer coefficient of the heat exchanger, reduced to the area of the radiating surface, was from 10.3±1.36 to 18.7±2.47 W·m–2·°C–1, when the condensation temperature was 12.8...21.9 °С higher than the temperature of atmospheric air. The operability of the condenser is shown both during the day and at night, in the presence of precipitation in the form of rain and snow, and a high level of cloudiness. The material capacity and filling of the refrigerant in the condenser are comparable to the characteristics of air-cooled condensers with forced air circulation. At the same time, it does not consume electricity. It can be used in stationary refrigeration systems (in data processing centers, commercial refrigeration equipment, air conditioners) to increase their energy efficiency